Molecular and morphological divergence in a pair of bird species and their ectoparasites - Whiteman, Noah K. (2009)
In an evolutionary context, parasites tend to be morphologically conservative relative to their hosts. However, the rate of neutral molecular evolution across many parasite lineages is faster than in their hosts. Although this relationship is apparent at the macroevolutionary scale, insight into the processes underpinning it may be gained through investigations at the microevolutionary scale. Birds and their ectoparasitic lice have served as important natural experiments in coevolution. Here, we compared mitochondrial and morphological divergence in 2 recently diverged avian host lineages and their parasites. Gaálapagos hawks (Buteo galapagoensis) are phenotypically divergent from their closest mainland relatives, the Swainson’s hawk (Buteo swainsoni). Both species are host to a feather louse species of Craspedorrhynchus (Insecta: Phthiraptera: Ischnocera, Philopteridae). We sequenced the 59 end of the mitochondrial gene cytochrome oxidase c subunit I (COI) from a set of hawks and lice. Although this fragment allowed unambiguous identification of host and parasite lineages on the islands and the mainland, only a single variable site was present in the 2 hosts, but 2 major Craspedorrhynchus clades divergent by 10% were recovered that sorted perfectly with host species. We found significant population genetic structure within the Galaápagos Craspedorrhynchus lineage. While the host species are highly differentiated phenotypically, the 2 Craspedorrhynchus louse lineages are phenotypically overlapping, although subtle but significant morphological differences exist.